Negotiating epistemic authority in parent-teacher conferences: non-native parents reclaiming agency against the backdrop of linguistic and cultural differences - Chiara Dalledonne Vandini; Davide Cino (Studi sulla Formazione, 2020)
In this paper we analyze the degree of participation, epistemic management, and authority performance during Parent-Teacher Conferences with non-native parents. Studies focusing on ethnic minority communities illustrate the dominance of the teacher’s epistemic authority (see Lareau and Weininger, 2003; Garcia-Sanchez and Orellana, 2007).  Describing differences in mastering both the expert and the institutional knowledge, Howard and Lipinoga (2010) illustrate how immigrated parents remain relatively silent during the report phase of the encounter. This paper reports data from eight parent-teacher conferences with non-native parents. We show how parents’ practices to accomplish and receive assessment confirm in part what has already been identified by the literature, but also adds new communicative “nuances”. We contend that also non-native parents could be able to challenge the teachers’ authority by questioning them and making the information from their territory of knowledge (i.e. the “child-at-home”) relevant. We advance that a detailed analysis of how the management of knowledge and the negotiation of epistemic authority occur in parent-teacher conferences will also help in critically rethinking some “pedagogical certainties” concerning school-family communication and their possible outcomes.